Brood stock maturity and artificial breeding of rainbow trout, Oncorhynchus mykiss (Walbaum) - Joshi, K D (Indian Journal of Fisheries, 2016)
The Norwegian rainbow trout, Oncorhynchus mykiss (Walbaum) was successfully reared and bred at the Experimental fishfarm, Chhirapani, Champawat (Uttarakhand). The stock attained sexual maturity during peak winter (December to February).The male attained maturity after completion of 2 years (average body weight: 180-820 g) and female after 3 years (averagebody weight: 900-1850g). Potential male and female brooders were segregated in separate ponds in November 2001 andstripping was conducted during February 2002 and December 2002, by dry method. Fecundity recorded was between547-1402 eggs kg-1 body weight. Eyed-egg stage was noticed after 23-46 days post-fertilization at ambient water temperaturebetween 4.5 to 8.5 0C. Incubation period was complete within 51-58 days (water temperature 6.5-12.0 0C) and 86-100 days(water temperature 4.5-7.5 0C). The cumulative survival recorded was between 42.2 to 88.9%. The resultant yolk-ladenhatchlings were of 14-17 mm size range.